Weak decays of doubly heavy baryons: the 1/2→1/2 case - Wang, Wei; Yu, Fu-Sheng; Zhao, Zhen-Xing (The European physical journal. C, Particles and fields, 2017)
Very recently, the LHCb collaboration has observed in the final state Λ c + K - π + π + a resonant structure that is identified as the doubly charmed baryon Ξ cc + + . Inspired by this observation, we investigate the weak decays of doubly heavy baryons Ξ cc + + , Ξ cc + , Ω cc + , Ξ bc ( ′ ) + , Ξ bc ( ′ ) 0 , Ω bc ( ′ ) 0 , Ξ bb 0 , Ξ bb - and Ω bb - and focus on the decays into spin 1 / 2 baryons in this paper. At the quark level these decay processes are induced by the c → d / s or b → u / c transitions, and the two spectator quarks can be viewed as a scalar or axial vector diquark. We first derive the hadronic form factors for these transitions in the light-front approach and then apply them to predict the partial widths for the semileptonic and nonleptonic decays of doubly heavy baryons. We find that the number of decay channels is sizable and can be examined in future measurements at experimental facilities like LHC, Belle II and CEPC.